The Relationship Between Basal Metabolism Index and Blood Sugar Levels Among Farmers: a Secondary Data Analysis of Non-Communicable Disease in Public Health Center of Pakusari, Jember Regency, Indonesia - Aji, Rizki Rama; Susanto, Tantut; Susumaningrum, Latifa Aini; Kholidi, Mokhlas; Yunanto, Rismawan Adi (Al-Hijrah Indonesia, 2023)
Obesity is a risk factor for hyperglycemia. Farmers are a group of people at risk of obesity and hyperglycemia due to a lifestyle that consumes foods high in fat and carbohydrates. The aim of this study wants to analyze the relationship between body mass index and blood sugar levels of farmers in the report of Integrated Development Post of Non-Communicable Disease (Posbindu PTM) Pakusari Jember Health Center. The survey analysis study used a retrospective cohort study. A design was used to analyze secondary data of Posbindu PTM Pakusari Jember Health Center registered from January to October 2020 among 345 farmers. A population of 345 farmers was selected by purposive sampling to be used as research samples. Characteristics of participants, height and weight, and random blood sugar levels were measured through a health monitoring book (KMS Posbindu PTM). The chi-Square test was used to answer the objective of the study. Among 146 farmers identified that 46.6% were obese and 45.9% were hyperglycemia. There was a relationship between body mass index and blood sugar levels in farmers (p-value = 0.000). Indirectly, body mass index affects blood sugar levels, manifesting as diabetes mellitus and other complications. Therefore, obesity should be identified as a risk factor associated with farmers' blood sugar levels.